Stress triggers and how to deal with them. (2nd March 2019) - Henley, Elaine
Abstract : There is a growing understanding of the effects that stress has on companion animals at all times of the year — living with humans is not easy! Elaine Henley explains the phenomonen of trigger-stacking and demonstrates how small changes in an animal's environment can have huge benefits.